Analysis of ANBK Planning on Influence Literacy and Numerization - Harahap, Alif Irfan; Fakhriza, M (Journal of Computer Science and Informatics Engineering, 2024)
Education is one of the things that humans need to obtain in order to be ready to face real life. This type of research is a type of field-based descriptive qualitative research. The research instruments include documentation, interviews and observations. Information obtained from investigating the implementation of ANBK is then processed and researched to produce recommendations for implementation. The research results show that the planning of semi-online-based ANBK facilities and infrastructure is more extensive than online-based ANBK. Semi-online ANBK complies with the rules and requires an appropriate server machine. Other facilities and infrastructure such as student computers, internet networks, and school personnel are also needed in addition to semi-online ANBK server computers. The infrastructure and facilities at SMA Nurul Iman Tanjung Morawa are more than sufficient and meet the requirements to facilitate the installation of semi-online ANBK. The implementation of the Computer-Based National Assessment (ANBK) at SMA Nurul Iman Tanjung Morawa has gone well during the examination process. In current Indonesian education, ANBK is a new concept. After providing a comprehensive overview of ANBK above, teachers must be ready to support students in adapting to the standards. With the help of students, homeroom teachers and operators introducing and transmitting the media and applications used in the ANBK Simulation.